(untitled) (Bangladesh Journal of Zoology, 2022)
Venomous snakes are one of the most dreadful animals globally that kill their victims by injecting venoms (toxic substances) using fangs. However, snakes are being used for numerous vital life-saving purposes, including antivenom and traditional medicines, pain killers, cancer treatment, cardiac arrest, paralysis, arthritis, anti-ageing, and cosmetics to leather products, foods, display and research. This study was conducted to investigate the current status, challenges and prospects of snake farming in Bangladesh using self-structured questionnaires surveys. In this study, in total, 281 snakes belonging to 12 species i.e., common krait Bungarus caeruleus, banded krait B. fasciatus, greater black krait Bungarus niger, monocled cobra Naja kaouthia, spectacled cobra Naja naja, king cobra Ophiophagus hannah, russell’s viper Daboia russelii, indian python Python molurus, common sand boa Eryx conicus, common cat snake Boiga trigonata, common wolf snake Lycodon aulicus and rat snake Ptyas mucosa were observed. This study also showed that the largest snake farm was at Patuakhali, where about 231 venomous snake individuals were reared, while 35 snakes were reared in Rajshahi farm, eight and seven snakes were reared in Rajbari and Gazipur farms, respectively. These snakes were collected from snake catchers/charmers and rescued from several places and nature. Snakes were fed on natural feeds (toad, frog, rat, and snake) and chickens. These farms had small to medium tin-shed building infrastructure with minimal facilities and used tanks, cages, and vivaria for snake rearing, breeding, and displaying. Snake farmers had not received any training, but some skilled snake handlers operated these farms. These snake farms did not keep managemental activities records and lack of proper design. These were not collected and preserved snake venom and were mainly involved in snake displaying. Although this study did not explore much information but snake farming may have great potential in Bangladesh; thus, more research is warranted on proper snake farming facilities. However, the government could be initiated the establishment of a modern and sophisticated snake farm for research, development, conservation, and venom collection including antivenom production and pharmaceutical purposes. Hence, the existing snake resources and skilled professionals may assist the government in snake farming activities. Bangladesh J. Zool. 50 (1): 121-133, 2022